Finasteride, 1 mg daily administration on male androgenetic alopecia in different age groups: 10-year follow-up - ROSSI, A.; CANTISANI, C.; SCARNò, M.; TRUCCHIA, A.; FORTUNA, M. C.; CALVIERI, S. (Dermatologic therapy, 2011)
ABSTRACT Finasteride 1 mg is indicated for the treatment of men with androgenetic alopecia (AGA). However, more than 5 years efficacy and safety has not been previously reported. To assess the efficacy over 10 years in different age groups of men with AGA. 118 men, between 20 and 61 years, with AGA receiving finasteride (1 mg/day), were enrolled in this uncontrolled study. Efficacy evaluation was assessed with standardized global photographs at T0,T1,T2,T5,T10. Statistical analysis was made using frequency tables and evaluating the chi‐square index with its p‐value. Better improvements are observed in patients older than 30 years (42.8% aged between 20 and 30 years did not improve also after 10 years) or with higher AGA grades (58.9% for AGA grade IV and 45.4% for AGA grade V had the first improvement just after 1 year). In 21% of cases, the treatment continuation beyond 5 years provided better results. Side effects were referred by 6% of the patients; nevertheless, some of them went on with treatment because of the great results. In our opinion, the result after the first year can help in predicting the effectiveness of the treatment. Its efficacy was not reduced as time goes on; in fact, a big proportion of subjects unchanged after 1 year, improved later on, maintaining a positive trend.